Enhancing Organizational Research Utilization: The Role of Decision Makers' Assumptions - Shrivastava, Paul; Mitroff, Ian I. (Academy of Management Review, 1984)
The limited use of organizational research for practical decision making is due in part to the differences in the assumptions made by organizational researchers in creating what they consider knowledge and organizational decision makers in using what they, in turn, call knowledge. The concept of frames of reference is proposed and developed as a basis for examining the differences between the assumptions made by decision makers and by researchers. Implications for the utilization of organizational research are discussed.